Manajemen Pelayanan Referensi di Perpustakaan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi - Innayatul Mubarokah (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2023)
This study aims to analyze the management of reference services at the Technical Implementation Unit (UPT) Library of Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi. The research focuses on how the reference service management is implemented as well as the supporting and inhibiting factors that influence its effectiveness. A qualitative descriptive approach was employed, with data collected through in-depth interviews, direct observation, and documentation. The findings reveal that the management of reference services at the UPT Library of UIN Sulthan Thaha Saifuddin Jambi still encounters several challenges, particularly in terms of limited human resources and inadequate facilities in the reference room. These limitations affect the overall quality and effectiveness of the services provided, which are expected to be a key pillar in supporting the academic information needs of the university’s community. To address these issues, the library has implemented strategies such as increasing the number of trained librarians and staff, as well as improving reference room facilities to make them more representative and responsive to users’ needs. These efforts are expected to enhance service quality, expand access to information, and foster a stronger culture of academic literacy within the university environment.